2020
DOI: 10.1021/acs.jchemed.0c00724
|View full text |Cite
|
Sign up to set email alerts
|

Turning Information Dissipation into Dissemination: Instagram as a Communication Enhancing Tool during the COVID-19 Pandemic and Beyond

Abstract: In the wake of the coronavirus disease 2019 (COVID-19) pandemic, staff and students at universities worldwide were forced to swiftly adapt to distance learning in order to continue with tertiary education. One of the main challenges we encountered during this period was a marked disconnect between staff and students, leading to lower motivation and engagement by both parties. To address this issue, we explored the social media platform Instagram as an interactive communication channel to engage first-year phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 13 publications
0
22
0
3
Order By: Relevance
“…Social media as a learning tool has found particular utility in situations where in-person instruction is limited or unavailable, as is currently the case due to the COVID-19 crisis. In response, chemical educators around the globe have implemented apps such as Instagram, WeChat, Facebook, and Discord to digitally connect with their students. The ChemClout Challenge may provide a framework for connecting student classmates during this remote period. Students are capable of creating these videos at home independently, with the help of family members, or potentially splicing videos together from multiple students as a group project.…”
Section: Compatibility With Distance Learningmentioning
confidence: 99%
“…Social media as a learning tool has found particular utility in situations where in-person instruction is limited or unavailable, as is currently the case due to the COVID-19 crisis. In response, chemical educators around the globe have implemented apps such as Instagram, WeChat, Facebook, and Discord to digitally connect with their students. The ChemClout Challenge may provide a framework for connecting student classmates during this remote period. Students are capable of creating these videos at home independently, with the help of family members, or potentially splicing videos together from multiple students as a group project.…”
Section: Compatibility With Distance Learningmentioning
confidence: 99%
“…Google Translations of the non-English comments indicated that students across languages and countries appreciated and shared these videos with their peers.Social media as a learning tool has found particular utility in situations where in-person instruction is limited or unavailable, as is currently the case due to the COVID-19 crisis. In response, chemical educators around the globe have implemented apps such as Instagram, WeChat, Facebook, and Discord to digitally connect with their students [33][34][35]. The ChemClout Challenge may provide a framework for connecting student classmates during this remote period.…”
mentioning
confidence: 99%
“…As depicted in Table 3 below, the number of research classified under the different regions of the world are mainly ten articles from the European Regions [German (Kernder et al, 2021), Europe (Arasli et al, 2020), United Kingdom (Arasli et al, 2020;Rendell, 2020;Scott, McGowan & Visram, 2021;Fumagalli, Dolmatzian & Shrum, 2021), Spain (Pérez-Escoda et al, 2020;, Finland (Malik et al, 2021), Italy (Fumagalli, Dolmatzian & Shrum, 2021), Sweden (Ye et al, 2020), Russia (Sharov, 2020)]; six articles from the South American Regions [Argentina (Herrera et al, 2020;Fumagalli, Dolmatzian & Shrum, 2021), Brazil (Galhardi et al, 2020;Forte & Pires, 2020;Moraes et al, 2020;Anacleto et al, 2021;Santos et al, 2020)]; six articles from the United States and Canadian Regions [USA (Hoyt et al, 2021;Mackey et al, 2020;Arasli et al, 2020;Cohen, Hoyt & Dull, 2020;Malik, Khan & Quan-Haase, 2021), Canada (Malik, Khan & Quan-Haase, 2021)]; five articles from the Southwest and Central Asia [Iran (Jahangiry et al, 2020;Niknam et al, 2021), Nepal (Ghimire, Dhungel & Pokhrel, 2020), Arabian Gulf (Ali et al, 2020), India (Srivastav et al, 2021)], 7 articles from the Western Asian Region [Palestine (Zabadi et al, 2020(Zabadi et al, , 2021, Turkey (Enver et al, 2020;Atas et al, 2020;Culha...…”
Section: Resultsmentioning
confidence: 99%